Ascendancy of unfolded protein response over glioblastoma: estimating progression, prognosis and survival. Issue 1 (2nd January 2023) - Gundamaraju, Rohit; Wu, Jian; William, Jonahunnatha Nesson George; Lu, Wenying; Jha, Niraj Kumar; Ramasamy, Subbiah; Rao, Pasupuleti Visweswara
ABSTRACT: Glioblastoma (GBM) is presented with a poor prognosis. The endoplasmic reticulum stress (ERS) has been implicated as a major contributor to disease progression and chemoresistance in GBM. Triggering ERS by chemical agents or genetic modulations is identified as some of the reasons for regulating gene expression and the pathogenesis of GBM. ERS initiates unfolded protein response (UPR), an integrated system useful in restoring homeostasis or inducing apoptosis. Modulation of UPR might have positive outcomes in GBM treatment as UPR inducers have been shown to alter cell survival and migration. In the current review, we have utilized GSE7806, a publicly available dataset from Gene Expression Omnibus (GEO), to evaluate the genes expressed during 6.5 hr and 18 hr, which can be comparable to the early and late-onset of the disease. Subsequently, we have elucidated the prognosis and survival information whilst the expression of these genes in the GBM was noted in previous studies. This is the first of its kind review summarizing the most recent gene information correlating UPR and GBM.